Exploring the Pangasinan-Cordillera connection the Pangasinenses and the Ibalois - Fernandez, Erwin S. (Cordillera Review : Journal of Philippine Culture and Society, 2009)
The history of ancient Pangasinan peoples is yet to be written. Rosario Cortes has written what has been regarded as groundbreaking narrative of Pangasinan history consisting of three volumes (1974, 1990a, 1990b). Nonetheless, its chapter on the period before 1572, titled "Prehispanic Culture," is rather sketchy and draws much of the data from the work of Diego Aduarte who was more interested in recording the successes of the Dominican missionary efforts to convert the stubborn Pangasinenses than in noting the latter's customs and traditions.